2019
DOI: 10.1080/17437199.2019.1625282
|View full text |Cite
|
Sign up to set email alerts
|

Identifying change processes in group-based health behaviour-change interventions: development of the mechanisms of action in group-based interventions (MAGI) framework

Abstract: Group-based interventions are widely used to promote health-related behaviour change. While processes operating in groups have been extensively described, it remains unclear how behaviour change is generated in group-based health-related behaviour-change interventions. Understanding how such interventions facilitate change is important to guide intervention design and process evaluations. We employed a mixed-methods approach to identify, map and define change processes operating in group-based behaviour-change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 66 publications
1
99
0
Order By: Relevance
“…As several clinical interventions building on social identity mechanism have already been implemented (e.g., Borek et al, 2019; Cruyws, Haslam, Dingle, Jetten, Haslam, Dingle, Haslam, & Jetten, 2014; Cruwys, Haslam, Fox & McMahon, 2015), we encourage clinicians and health professionals to apply a broader view of social identification when planning such interventions, accounting for the multi‐level nature of this psychological construct. Hence, group‐level processes, individual‐level processes as well as their interaction should be captured in interventions and treatments.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…As several clinical interventions building on social identity mechanism have already been implemented (e.g., Borek et al, 2019; Cruyws, Haslam, Dingle, Jetten, Haslam, Dingle, Haslam, & Jetten, 2014; Cruwys, Haslam, Fox & McMahon, 2015), we encourage clinicians and health professionals to apply a broader view of social identification when planning such interventions, accounting for the multi‐level nature of this psychological construct. Hence, group‐level processes, individual‐level processes as well as their interaction should be captured in interventions and treatments.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Similarly, studies of group-based chronic disease self-management programmes showed that groups helped enhance selfefficacy for using self-management and coping strategies by providing opportunities for sharing experiences, social comparisons, and support (Abraham & Gardner, 2009;Barlow, Bancroft, & Turner, 2005;Rogers, Gately, Kennedy, & Sanders, 2009). Yet, the potential benefits of group support may not always be maximized by group facilitators in such interventions (Borek et al, 2019;Hughes et al, 2018). Yet, the potential benefits of group support may not always be maximized by group facilitators in such interventions (Borek et al, 2019;Hughes et al, 2018).…”
Section: Design Qualitativementioning
confidence: 99%
“…Research has also shown that developing a shared social identity is important in promoting health and engagement with group interventions (Tarrant, Hagger, & Farrow, 2012;Tarrant et al, 2017). Yet, the potential benefits of group support may not always be maximized by group facilitators in such interventions (Borek et al, 2019;Hughes et al, 2018). Previous studies have explored participants' experiences of health interventions in general.…”
mentioning
confidence: 99%
“…Group interventions can present opportunities for costs savings by treating more than one person at the same time. In addition, advocates of group interventions have proposed mechanisms of action that are important for behaviour change that arise from being in a group that are not present in individual therapies, such as inter-personal change processes, universalisation, social comparison, social learning and modelling [6,7,9,10]. The role of group process and dynamics in these mechanisms is contested, with some believing that these mechanisms of action can be triggered by individual-therapist interaction [11] and others proposing that the group aspect is an essential part of the intervention [12].…”
Section: Group Interventions In Healthcarementioning
confidence: 99%